Drama Assistance Using the Sociodrama Model at SMP N 2 Medan - Trisnawati Hutagalung; Azhar Umar; Ayu Nadira Wulandari (Universitas Negeri Medan, 2025)
The problems faced by partners so far are: (1) lack of appropriate methods to use in teaching, (2) lack of ability of Indonesian language teachers in drama, (3) teachers at SMP N 2 Medan do not hone their drama skills because there is no guidance that is more proficient in theory and practice. The objectives of this community service activity are: (1) to provide drama assistance using the sociodrama model as one of the innovative drama models, (2) to provide assistance in drama practice of students at SMP N 2 Medan, (3) to provide ongoing guidance and assistance. The benefits obtained by partners from this activity are: (1) to improve the drama skills using the sociodrama model of SMP N 2 Medan teachers so that it can be used as a method in teaching; (2) to attract the attention of students and motivate students to be enthusiastic about learning. The approach method used to overcome partner problems is the method of education, training and mentoring intensively and continuously. The real output results of community service activities are (1) One scientific article published through an online ISSN journal from a national seminar; (2) Publication in print/ online mass media/ university repositories; (3) Learning Videos.